2011
DOI: 10.3109/17483107.2011.574310
|View full text |Cite
|
Sign up to set email alerts
|

Virtual reality games for rehabilitation of people with stroke: perspectives from the users

Abstract: PURPOSE. The purpose of this study is to evaluate the feasibility and users' perspectives of a novel virtual reality (VR) game-based rehabilitation intervention for people with stroke. METHOD. Six people with upper limb hemiplegia participated in a 6-week intervention that involved VR games. A series of eight progressively complex games was developed that required participants to navigate a submarine in a virtual ocean environment. Movement of the submarine was directed by forces applied to an arm interface by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
88
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(100 citation statements)
references
References 34 publications
5
88
0
2
Order By: Relevance
“…A likely explanation may be found in game design: Where Laver et al 45 used an off-the-shelf system without patient-specific adaptations, the exergames used in this study were specifically designed and developed for rehabilitation and were adapted to the cognitive and physical limitations of functionally impaired persons or elderly. This explanation is in line with Cameirão et al, 46 who found high acceptance of a gaming system specifically designed to treat post-stroke motor deficits, and with Lewis et al, 4 who demonstrated positive results for newly developed exergames aimed to improve stroke patients' arm function. Our findings also corroborate the high acceptance rates of specifically designed exergames found by Backlund et al 47 Thirteen of the 16 participants (81 percent) completed the full allocated training program and attended the retesting assessments.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…A likely explanation may be found in game design: Where Laver et al 45 used an off-the-shelf system without patient-specific adaptations, the exergames used in this study were specifically designed and developed for rehabilitation and were adapted to the cognitive and physical limitations of functionally impaired persons or elderly. This explanation is in line with Cameirão et al, 46 who found high acceptance of a gaming system specifically designed to treat post-stroke motor deficits, and with Lewis et al, 4 who demonstrated positive results for newly developed exergames aimed to improve stroke patients' arm function. Our findings also corroborate the high acceptance rates of specifically designed exergames found by Backlund et al 47 Thirteen of the 16 participants (81 percent) completed the full allocated training program and attended the retesting assessments.…”
Section: Discussionsupporting
confidence: 69%
“…3 However, further functional gains after acute rehabilitation are possible, even in the chronic stage. 1,4 Following a stroke, approximately 80 percent of patients experience hemiparesis accompanied by considerable walking deficits. 5 The typical ''hemiplegic gait'' post-stroke is associated with several negative consequences (e.g., gait asymmetry, reduced walking velocity, cadence, and stride length).…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, Lewis et al found that for some participants, challenging themselves during computer-based games and observing progress through levels of difficulty and real-time score feedback meant encouragement to continue trying [32]. Some authors consider providing a score following the playing of a computer game important, because scores and similar feedback allow for performance feedback, which promotes learning [14,33].…”
Section: Discussionmentioning
confidence: 99%
“…Stroke rehabilitation can be a long process; as such, much of it takes place in the home setting. However adherence to home exercise programmes (HEPs) is poor with a recent study finding 79% of patients in the community stopped doing their HEP as prescribed after two days [3]. A perceived lack of support from physiotherapists was the most frequently mentioned factor associated with lack of compliance.…”
Section: Introductionmentioning
confidence: 99%